2018
DOI: 10.1111/apa.14569
|View full text |Cite
|
Sign up to set email alerts
|

Bone and joint infections in infants under three months of age

Abstract: Streptococcus agalactiae was the most common cause of BJI in infants under three months. Orthopaedic sequelae were rare, but severe, and required long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…The aetiology, however, largely depends on the patient’s age ( Table 1 ). A recent multicentre study conducted in France on 71 patients aged under 3 months reported that Streptococcus agalactiae is the main community-acquired pathogen accounting for 45% of these cases, followed by S. aureus (22% of all cases) which was the most frequent microorganism in infants aged over 2 months, and Escherichia coli (18%) [ 22 ]. These findings were confirmed by Juchler et al in infants aged 0–6 months, reporting S. aureus , S. agalactiae , and E. coli as the most frequently isolated pathogens, accounting for 31%, 15%, and 8% of these cases, respectively [ 23 ].…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…The aetiology, however, largely depends on the patient’s age ( Table 1 ). A recent multicentre study conducted in France on 71 patients aged under 3 months reported that Streptococcus agalactiae is the main community-acquired pathogen accounting for 45% of these cases, followed by S. aureus (22% of all cases) which was the most frequent microorganism in infants aged over 2 months, and Escherichia coli (18%) [ 22 ]. These findings were confirmed by Juchler et al in infants aged 0–6 months, reporting S. aureus , S. agalactiae , and E. coli as the most frequently isolated pathogens, accounting for 31%, 15%, and 8% of these cases, respectively [ 23 ].…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…These findings were confirmed by Juchler et al in infants aged 0–6 months, reporting S. aureus , S. agalactiae , and E. coli as the most frequently isolated pathogens, accounting for 31%, 15%, and 8% of these cases, respectively [ 23 ]. In this age group, both studies observed that Klebsiella pneumoniae and Candida albicans are particularly frequent nosocomial pathogens, and they each account for 7% of cases [ 22 ]. Among children aged between 6 months and 5 years, K. kingae is the most frequent cause of osteoarticular infections, accounting for half of these cases [ 23 ].…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations